2004
DOI: 10.1111/j.1365-2648.2004.03205.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of infant‐feeding decision‐making among urban economically disadvantaged pregnant adolescents

Abstract: Consistent with the Theory of Planned Behaviour and other research, attitudes, perceived social influences, and perceived control factors were influential to adolescents when choosing infant feeding methods. The findings suggest that adolescents need education on decision-making, and are being used to fine-tune the interventions of a randomized clinical trial to investigate promoting and supporting breastfeeding among adolescent mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 25 publications
3
63
0
5
Order By: Relevance
“…Previous discussions of ambivalence regarding breast-feeding have focused on ambivalence due to societal norms and other external pressures (Kaufman, Deenadayalan, and Karpati 2010;Wambach and Koehn 2004). However, the experientially based ethnographic data collected from this group of Brazilian women suggest that resistance to unplanned motherhood and to the physicality of breast-feeding may be a central determinant of their infant-feeding decisions.…”
Section: Discussionmentioning
confidence: 88%
“…Previous discussions of ambivalence regarding breast-feeding have focused on ambivalence due to societal norms and other external pressures (Kaufman, Deenadayalan, and Karpati 2010;Wambach and Koehn 2004). However, the experientially based ethnographic data collected from this group of Brazilian women suggest that resistance to unplanned motherhood and to the physicality of breast-feeding may be a central determinant of their infant-feeding decisions.…”
Section: Discussionmentioning
confidence: 88%
“…Giles et al 21 showed that young people have limited exposure to breastfeeding, are unclear about the benefits of breastfeeding and find breastfeeding in public embarrassing. Knowledge about the benefits of breastfeeding increases in pregancy 10,11 but breastfeeding in public continues to be viewed highly negatively 9,22--24 . It appears easier to educate mothers about the benefits of breastfeeding than to alter perceptions of the public acceptability of breastfeeding.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…There are defined limits on the generalisability of findings from qualitative studies 19 In the UK teenage mothers are among the least likely to breastfeed 1 . Studies have been carried out into the reasons why those from disadvantaged groups do not initiate and continue breastfeeding, many of which are linked to the theory of planned behaviour 10,11,20 . Such studies conclude that family influences and concerns about breastfeeding in public significantly influence infant feeding behaviour 20 and that breastfeeding can be seen as a 'morally inappropriate' behaviour by teenagers 11 .…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire studies of pregnant and mothering teenagers in the US and UK have established that they know that breastfeeding is best for their babies' health and promotes bonding, and that more young mothers intend to breastfeed than actually start (Shaw et al 2003, Wambach and Koehn 2004, Hunter 2008, Mossman et al 2008. It is likely that young women's experiences in the early postnatal period impact on their feeding decisions.…”
Section: Introductionmentioning
confidence: 99%